2000
DOI: 10.1103/physrevlett.84.863
|View full text |Cite
|
Sign up to set email alerts
|

Electron Correlations Observed through Intensity Interferometry

Abstract: Intensity interferometry was applied to study electron correlations in doubly ionizing ion-atom collisions. In this method, the probability to find two electrons emitted in the same double ionization event with a certain momentum difference is compared to the corresponding probability for two uncorrelated electrons from two independent events. The ratio of both probabilities, the so-called correlation function, is found to sensitively reveal electron correlation effects, but it is rather insensitive to the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 12 publications
0
55
0
Order By: Relevance
“…A subtle structure of correlated electron dynamics during the non-sequential multiple ionization process has been investigated in a series of recent experiments using a "reaction microscope". The latter allows to calculate the full momentum vectors of the recoil ions and electrons from time-of-flight and position measurements on the detectors [268].…”
Section: More Complex Systemsmentioning
confidence: 99%
“…A subtle structure of correlated electron dynamics during the non-sequential multiple ionization process has been investigated in a series of recent experiments using a "reaction microscope". The latter allows to calculate the full momentum vectors of the recoil ions and electrons from time-of-flight and position measurements on the detectors [268].…”
Section: More Complex Systemsmentioning
confidence: 99%
“…Recently, electron correlations have been investigated by inspecting the so-called correlation function R (Schulz et al 2000a;Feuerstein et al 2001a;Gerchikov and Sheinermann 2001;Schulz et al 2001a;Gerchikov et al 2002). Here, the probability to find two electrons emitted in the same multiple ionisation event with a certain momentum difference is compared to the corresponding probability for two independent electrons emitted in two different collisions.…”
Section: Double Ionisation At Small and Large Perturbationsmentioning
confidence: 99%
“…Since the projectile brings no electron into the collision, the cusp peak is formed due to the ECC mechanism only. Previous studies on the correlation function have shown that it is the final-state e-e interaction that primarily determines the energy and angular distribution of the DI electrons [15,16]. The final state of the process (1) investigated in the experiment and that of the double ECC studied in this work are similar: Two repelling electrons move in the attractive Coulomb field of a heavy charged particle in the same direction with small relative velocity.…”
Section: Introductionmentioning
confidence: 70%
“…More details can be explored by measuring the angular and energy distribution of the emitted electrons which has become available recently due to an adaptation of the coincidence electron detection technique in the field. The so-called correlation functions [15,16], the role of first-order and second-order processes in the ejection mechanism [17] and some characteristic structures in the electron distributions [13] have been the focus of the studies, while the threshold behavior of the DI process received less interest.…”
Section: Introductionmentioning
confidence: 99%